2015
DOI: 10.1093/nar/gkv269
|View full text |Cite
|
Sign up to set email alerts
|

RNA editing by T7 RNA polymerase bypasses InDel mutations causing unexpected phenotypic changes

Abstract: DNA-dependent T7 RNA polymerase (T7 RNAP) is the most powerful tool for both gene expression and in vitro transcription. By using a Next Generation Sequencing (NGS) approach we have analyzed the polymorphism of a T7 RNAP-generated mRNA pool of the mboIIM2 gene. We find that the enzyme displays a relatively high level of template-dependent transcriptional infidelity. The nucleotide misincorporations and multiple insertions in A/T-rich tracts of homopolymers in mRNA (0.20 and 0.089%, respectively) cause epigenet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(33 citation statements)
references
References 78 publications
1
32
0
Order By: Relevance
“…This mechanism of expression is supported by examination of sequences corresponding to different potyviruses present in the virome of the AM-MB2 plant, which showed results consistent with polymerase slippage in equivalent G 2 A 6 motifs for SPV2 and SPVC (see Table S7 in the supplemental material). Moreover, our experiments designed to identify translational frameshifting in WGE failed to show a noticeable production of truncated frameshifted protein products, and the presence of minor products compatible in size could be also generated by T7 polymerase slippage, as shown by others (14,49,50). Consistent with our view that viral RNA polymerase slippage is the most likely mechanism of production of out-of-frame products in potyviruses, the transient expression of wild-type P1 sequence out of the viral infection context resulted in the production only of P1-derived peptides when analyzed with the sensitive mass spectrometry technique (Fig.…”
Section: Discussionmentioning
confidence: 87%
“…This mechanism of expression is supported by examination of sequences corresponding to different potyviruses present in the virome of the AM-MB2 plant, which showed results consistent with polymerase slippage in equivalent G 2 A 6 motifs for SPV2 and SPVC (see Table S7 in the supplemental material). Moreover, our experiments designed to identify translational frameshifting in WGE failed to show a noticeable production of truncated frameshifted protein products, and the presence of minor products compatible in size could be also generated by T7 polymerase slippage, as shown by others (14,49,50). Consistent with our view that viral RNA polymerase slippage is the most likely mechanism of production of out-of-frame products in potyviruses, the transient expression of wild-type P1 sequence out of the viral infection context resulted in the production only of P1-derived peptides when analyzed with the sensitive mass spectrometry technique (Fig.…”
Section: Discussionmentioning
confidence: 87%
“…The reliability of T7 RNA polymerase regresses as transcript length increases, usually resulting in the addition of untemplated nucleotides to the 3′ end . Next Generation Sequencing study on a T7 RNAP‐generated mRNA pool has also revealed a relatively high level of template‐dependent transcriptional infidelity . In addition, RNA species generated from in vitro transcription do not consist of necessary natural modifications because of the absence of posttranscriptional modification machineries.…”
Section: In Vitro Transcription and Enzymatic Production Of Rna Agentsmentioning
confidence: 99%
“…Productive transcriptional slippage at such sites involves unwinding-rewinding of the RNA:DNA hybrid which is not sensed by RNAP active site and hereby does not lead to enzyme backtracking and mRNA correction. Forward and backward mRNA slippage generates insertion/deletion errors in nascent transcripts, resulting in shift of reading frame [ 6 ]. It is known that the error rate of transcripts generated by E. coli RNAP in vivo is significantly high, roughly between the values of 10 −5 and 10 −3 per residue [ 7 ], and even higher for T7 RNAP [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Forward and backward mRNA slippage generates insertion/deletion errors in nascent transcripts, resulting in shift of reading frame [ 6 ]. It is known that the error rate of transcripts generated by E. coli RNAP in vivo is significantly high, roughly between the values of 10 −5 and 10 −3 per residue [ 7 ], and even higher for T7 RNAP [ 6 ]. Insertion/deletion (indels) type of transcriptional errors may be considered as ambiguous.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation